A Thematic Analysis Investigating the Impact of Positive Behavioral Support Training on the Lives of Service Providers: “It Makes You Think Differently” - Walsh, R. Stephen; McClean, Brian; Doyle, Nancy; Ryan, Suzanne; Scarborough-Lang, Sammy-Jo; Rishton, Anna; Dagnall, Neil (Frontiers in Psychology, 2019)
Positive Behavioural Support (PBS) employs applied behavioural analysis to enhance the quality of life of people who behave in challenging ways. PBS builds on the straightforward and intuitively appealing notion that if people know how to control their environments, they will have less need to behave in challenging ways. Accordingly, PBS focuses on the perspective of those who have behavioural issues, and assesses success via reduction in incidences of challenging behaviours. The qualitative research presented in this report approaches PBS from a different viewpoint and, using thematic analysis, considers the impact of PBS training on the lived experience of staff who deliver services. Thirteen support staff who work for a company supplying social care and supported living services for people with learning disabilities and complex needs in the North West of England took part. Analysis of interviews identified five major themes. These were 1) Training: Enjoyable and useful; 2) Widening of perspective: Different ways of thinking; 3) Increased competence: Better outcomes; 4) Spill over into private lives: increased tolerance in relationships; and 5) Reflecting on practice and moving to a holistic view: ‘I am aware that people…are not just being naughty’. These themes evidenced personal growth on the part of service providers receiving training. Explicitly, participants demonstrated that greater awareness of PBS equipped recipients with a ‘different way of thinking’ and the technical knowledge required to realise this.